Dinamika Peran Negara dalam Proses Liberalisasi dan Privatisasi - Syamsul Ma'arif (Magister Administrasi Publik, 2006)
Liberalization and privatization are often associated with global demands for termination of state interference in business. The policy often result in dispute between neoliberalism and socialism. Neoliberalism perceives state interference in economic area as bad, damaging, an inefficient to economic life. State, which conduct the operation in political power logic, is perceived less or even not give the place for the expanding of healthy market structure and competitive. While socialism perceived state as central figure of economic with the centralized planning instrument and the ownership be on the hand of state. As economic system, socialism can be understood as an economic system in which the means of production, distribution, and exchange are publicly owned and operate. Since socialism assumes state as the most representative organization, so the meaning of owned and operated by public means the power of ownership and the mode of operation be on the hand of state. As political ideology, in its connection wit the economic control, socialism believe that the state should develop the economic planning and control on market operation. This paper prove that neoliberalism and the philosophy demands for termination of state role, in the reality, suffer a kind of paradox. On one hand, it trust market excellence so much over state. But on the other hand, it requires the active role of state to return the free market idea.